The imprint of windblown dust from the North American Southwest on the California Channel Islands and Pacific Ocean sediments. (1st June 2021) - Jardine, G.E.; Crocker, A.J.; Bailey, I.; Cooper, M.J.; Milton, J.A.; Wilson, P.A.
Abstract: Climate projections for the North American Southwest (NASW) predict an increasing frequency and duration of droughts over the 21st century in response to human-induced warming, with potentially severe economic and social consequences. The geological record provides a way to contextualise this prediction because of the past occurrence of abrupt hemispheric warming events and sustained intervals of atmospheric carbon dioxide loading equivalent to those projected for AD 2100 (between ∼500 and 900 ppmv). Yet, terrestrial climate archives are typically too short and incomplete to provide a full record of these events. In principle, drill cores from deep sea sediments in the eastern Pacific Ocean can be used to overcome this problem because they contain long records of continental dust and distal riverine-supplied sediments from North America. Yet our limited understanding of the provenance and transport pathways of these sediments impedes use of these marine archives for this purpose. Here we present radiogenic isotope data (Sr, Nd and Pb) from known NASW dust-producing hot spots – playa lakes in the Mojave Desert, Quaternary silts mantling the California Channel Islands and the terrigenous fraction from marine sediments of the eastern Pacific Ocean, supported by new maps of bedrock isotopic composition in the NASW. We use these and published data sets to infer the origin of playa lake silts in the Mojave Desert and the source of windblown sediments to the California Channel Islands and nearby ocean basins. Our Results rule out a significant contribution from the distal tails of either the Pacific Asian dust plume or the North African dust plume to the Quaternary Channel Island silt mantles, corroborating the suggestion that they are aeolian in origin and sourced from the NASW on the Santa Ana winds. We identify the Outer California Borderland basins as an attractive proposition for studying past dust flux and palaeoaridity in the North American Southwest. Highlights: We fingerprinted dust sources and sinks in the North American Southwest, NASW. NASW playa lakes display small Pb, Nd and Sr isotopic range compared to bedrock. California Channel Island silt mantles are windblown from the NASW. Influence of Asian and African dust on the California borderlands is negligible. Windblown dust to the Pacific Ocean is traced using Sr, Nd and Pb isotopes.